Characterization of collagen from freshwater fish skin - Mohamad Razali, Umi Hartina; Bakar, Jamilah; Mat Hashim, Dzulkifly; Sazili, Awis Qurni (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
Collagen extraction from the skins of barramundi and tilapia were carried out using mild acid treatment. The yield and physico-chemical properties of the extracted collagen were evaluated. The yield, proximate composition, colour, odour, and amino acid profiling of the extracted collagen was determined. The collagen, obtained from the skins of barramundi (Lates calcarifer) and red tilapia (Oreochromis nilotica) had a yield between 40 % and 44 % by weight. The colour of tilapia skin collagen is different from that of barramundi skin collagen. Both of the collagens were basically colourless and odourless. The predominant amino acids were glycine, proline, alanine and arginine.